Trinity and Apologetics In the Theology of St. Augustine - Cavadini, John C. (Modern theology, 2013)
This article examines Trinitarian themes in St. Augustine's City of God and in his On the Trinity. It argues that the scope and intention of the latter work can be clarified to some extent by noticing the apologetic commitments entailed in the exposition of the doctrine of the Trinity in the former. It argues against the tendency of some recent scholarship to restrict the intelligibility of the On the Trinity to converted Christians, even as it also defends the irreducibility of the doctrine of the Trinity, in Augustine's thinking, to any doctrine of pagan learning. Without prejudice to recent scholarly clarifications of the polemical origins of some of the arguments in the On the Trinity, the article argues (in effect) that the work is more than the sum of its polemical parts, and is intentionally addressed by Augustine to a wide readership, deliberately unspecified in identity except insofar as they are united as "human beings who are seeking God." Just as ancient apologetics, including Augustine's, was addressed to a variety of people, pagan and Christian, in various states of conviction and conversion, so the On the Trinity is meant to address many types of readers, at various levels of conversion and understanding, hoping to bring all of them closer to—or to confirm and deepen their participation in—the true worship of the one true God, without which, Augustine believes, no one can ultimately find the God they seek.